Analisis Bibliometrik Perkembangan Penelitian Material Flow Cost Accounting (MFCA) Berdasarkan Data Scopus - Zul Azmi; Suraya Nadella; Della Apriliana (CV. ITTC INDONESIA, 2026)
Material Flow Cost Accounting (MFCA) is an environmental management accounting approach that aims to improve material efficiency while reducing environmental impact. This study aims to analyze the development of scientific publications related to MFCA through a bibliometric literature review. Data were collected using the Scopus database using the keyword